THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.
Publisher: Zenodo

Inclusive education in Macao: Teachers' perceptions and attitudes - Correia, Ana; Teixeira, Vitor; Monteiro, Elisa; Kuok, A. C. H. (University of Saint Joseph, 2017)

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.
8 citations (Crossref) [2022-11-01]

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
9 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2018.1514762
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
7 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2017.1414318
Keywords: Disability; education policy; inclusive education; special education; special education needs